Personality Traits of Float Pool Nurses at King Fahad Hospital in Medina, Saudi Arabia - Ayman Ateq Al Amri; Glezzeelyne Pascual Pascua; Yasir Omar Ashour; Mohammed Munawer Abu Ruhaylah; Fadzrina Bibih Alih (Humanistic Network for Science and Technology (HNST), 2017)
Nurses play an essential role in providing optimal patient care. However, issues such as nursing shortage, increasing rate of absenteeism affects the quality of nursing care. Creating a solution to address these issues is of paramount importance. Hence, float pool nurses is one of strategies viewed to be used to face these challenges. Furthermore, this research aimed to delve on the personality traits of float pool nurses and unit-based nurses at work and determine if the float pool nurses have different personality traits than unit-based nurses. A quantitative, descriptive design was employed in this study wherein data were collected through a selfadministered 56-item questionnaire distributed to 80 registered nurses (40 float pool nurses and 40 unit-based nurses) in King Fahad Hospital in Medina, Saudi Arabia and the results were: Majority of the responses of both respondents shows a consistent preference of neither accurate nor inaccurate of personality factors (Mean = 2.91), sixty-eight percent or 34 out of 50 personality traits items revealed to be significant. Findings indicate that float pool nurses were open to change, creating new ideas, interested to work in new environment. However, they need more support to understand the new situation. Keywords: Float pool, Float nurses, Floating, Staffing shortage, Alternative staffing